Pengaruh Harga Dan Kualitas Produk Terhadap Minat Beli Konsumen Pada Usaha Aqiqah Karya Tanjung Farm Mojokerto - Subagio, N. Ari; Munir, Akhmad; Maulidah, Hamimah (IJABAH, 2023)
This research was conducted to examine the effect of price and product quality on consumer buying interest in the Aqiqah Karya Tanjung Farm Mojokerto business. The data analysis technique used in this research is multiple linear regression analysis using SPSS. The population of this study are all consumers who have made purchases at Aqiqah Karya Tanjung Farm Mojokerto. The sampling technique for this study used non-probability sampling with purposive sampling method, with a total sample of 80 respondents. The primary data of this study were obtained by distributing questionnaires to all samples. The results of this study indicate that price has no significant effect while product quality has a significant effect on consumer buying interest in the Aqiqah Karya Tanjung Farm Mojokerto business. So it can be concluded that consumers are not price sensitive as long as the product quality remains good. The implication, companies can use the quality of the products produced as a competitive advantage in their business competition.